From Anxiety to Assurance: A Mixed-Methods Journey Into Service Innovation, Trust and Customer Relationships - Bağcı, Rifgi Buğra; Tasçioglu, Mertcan; Bağcı, Rıfgı Buğra (Emerald Publishing, 2025)
Purpose – Grounded in Resource Dependence Theory and Social Exchange Theory, this study aims to examine the relationship between service innovation, trust dimensions (competence, contractual and goodwill) and relational performance. In addition, it analyzes the mediating role of trust types and the moderating effect of relationship anxiety. The authors also analyze various configurations that lead to higher relational performance and different dimensions of trust.Design/methodology/approach – This study uses a mixed-methods approach, integrating quantitative data from 232 managers of top 500 organizations and qualitative insights from in-depth interviews with five suppliers and five customers. Quantitative data is analyzed using partial least squares structural equation modeling (PLS-SEM) and FsQCA, while qualitative data is examined through thematic analysis.Findings – PLS-SEM results indicate that competence trust is the only trust dimension mediating the service innovation-relational performance link, while relationship anxiety unexpectedly strengthens the relationship between service innovation and trust. Service innovation positively influences all trust types, which in turn enhances relational performance. FsQCA findings highlight that positive service innovation and the negation of relationship anxiety are central to trust formation and relational performance. Qualitative insights further reveal that buyers prioritize competence over goodwill and contractual trust, with long- term business to business (B2B) relationships and technical proficiency overriding the effects of relationship anxiety.Originality/value – This study advances the literature by linking suppliers’ service innovation to relational performance, addressing prior research calls and incorporating diverse outcome variables. It further demonstrates how different trust dimensions yield distinct effects in B2B relationships, refining our understanding of trust–performance relationships. In addition, it contributes by examining mediators and introducing relationship anxiety as a moderator, offering new insights into its impact on relational outcomes.
Keywords: Service innovation; Trust; Business-to-business services; Mixed-methods